Pengaruh Living Values Education Program Terhadap Penguatan Karakter Nasionalisme - Runi Anggriani; Asrin Asrin; Ilham Syahrul Jiwandono (Pendagogia: Jurnal Pendidikan Dasar, 2021)
This study aims to determine whether or not there is an effect of the Living Values ​​Education Program assisted by the Value Clarification Technique on increasing the nationalistic character of students in Civics learning at SDN Woro cluster for the academic year 2020/2021. This research is a Quasi Experimental Quantitative Research conducted at SDN Gugus Woro. The population of this study were all fifth grade students of SDN Gugus Woro, totaling 61 people. The sample of this research is SDN Inpres 1 Woro and SDN Inpres 2 Woro, totaling 21 people. The data collection technique in this study used a nationalism character questionnaire. The results of this study after the research hypothesis was tested by t-test obtained tcount = 3,406. While the value of ttable = 2.228. Based on the hypothesis testing criteria, if tcount > ttable then Ho is rejected and Ha is accepted, if tcount < ttable then Ho is accepted and Ha is rejected. Because tcount > ttable, Ho is rejected and Ha is accepted, meaning that the use of LVEP assisted by the VCT learning model has an effect on strengthening the nationalist character of fifth grade students at SDN Gugus Woro